2009
DOI: 10.1111/j.1600-0536.2009.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact hypersensitivity and allergic contact dermatitis among school children and teenagers with eczema

Abstract: Background: Patch testing is an essential procedure in the investigation of eczema in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
47
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 25 publications
4
47
0
2
Order By: Relevance
“…However, the exact relationship between atopic dermatitis and allergic contact dermatitis is somewhat complex and controversial as the studies are conflicting (2,3). Our case series may support this notion, as a probable contact dermatitis to the car seat was observed in 12 ⁄ 21 atopic patients (57%), compared with 9 ⁄ 21 patients (43%) without an atopic background.…”
Section: Discussionsupporting
confidence: 74%
“…However, the exact relationship between atopic dermatitis and allergic contact dermatitis is somewhat complex and controversial as the studies are conflicting (2,3). Our case series may support this notion, as a probable contact dermatitis to the car seat was observed in 12 ⁄ 21 atopic patients (57%), compared with 9 ⁄ 21 patients (43%) without an atopic background.…”
Section: Discussionsupporting
confidence: 74%
“…In the literature, most studies stated NS as being the most common contact allergen, at a frequency of 14.9%-59.1% in patients with positive patch test reactions (2)(3)5,7,17). Accordingly, in our study population, NS was the most common positive reaction with a frequency of 37.8% (17/45).…”
Section: Discussionmentioning
confidence: 84%
“…These may be taken into account as warning points for investigating children with AD for possible contact sensitization. In the literature, the frequency of contact sensitization of children with AD was reported as 6.2% to 89% in different countries worldwide (2)(3)(4)(5)(6)(7). This wide range of frequency may be due to the usage of different contact allergen panels and inclusion of different age groups of children in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in contrast with previously reported rates not only in the general population, 18 but also in older children. 5,14 However, very recent studies 19,20 have shown a higher prevalence of positive patch test reactions in younger male children.…”
Section: Discussionmentioning
confidence: 98%